Evaluation of Salinity Tolerance of Rice Varieties under Laboratory Conditions (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
In this article, in addition to various biotic stresses in rice cultivation today, abiotic stresses also have a negative effect on rice productivity. One of them is salinity stress, and the article evaluates the resistance of rice varieties and samples to this stress in laboratory conditions. Durability was analyzed in four different concentrations of NaCl salt (0.5, 1.0, 1.5 and 2.0%) and in control options. According to the results of the analysis, the salinity resistance characteristics of "Sadaf", "Tolmas + Marvarid" varieties and 4 sample rows were described.